Surveying Clinicians by Web: Current Issues in Design and Administration. (September 2013) - Dykema, Jennifer; Jones, Nathan R.; Piché, Tara; Stevenson, John
The versatility, speed, and reduced costs with which web surveys can be conducted with clinicians are often offset by low response rates. Drawing on best practices and general recommendations in the literature, we provide an evidence-based overview of methods for conducting online surveys with providers. We highlight important advantages and disadvantages of conducting provider surveys online and include a review of differences in response rates between web and mail surveys of clinicians. When administered online, design-based features affect rates of survey participation and data quality. We examine features likely to have an impact including sample frames, incentives, contacts (type, timing, and content), mixed-mode approaches, and questionnaire length. We make several recommendations regarding optimal web-based designs, but more empirical research is needed, particularly with regard to identifying which combinations of incentive and contact approaches yield the highest response rates and are the most cost-effective.